DEVELOPMENT PROSPECTS OF THE MODERN ELECTRONIC UNIVERSITY - Viunenko, Oleksandr (Sworld-Us Conference proceedings, 2023)
With the development of technology, e-learning is becoming an increasingly popular method of education. Electronic universities, or e-universities, are a form of electronic learning that has the potential to revolutionize our approach to higher education.